2018
DOI: 10.1007/s10840-018-0424-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ICDs and CRTs in patients with chronic kidney disease: a meta-analysis of 21,000 patients

Abstract: The use of ICDs is associated with lower all-cause mortality in observational studies of CKD patients. CRT use was also associated with lower all-cause mortality in CKD patients in comparison to ICDs. A randomized controlled trial is required to definitively define the role of ICDs/CRTs in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…From a large meta-analysis of published studies, it is known that the use of CRT in patients with CKD positively affects patient survival; however, the mechanism by which this occurs is unknown. e authors of our study strongly recommend that a randomized controlled trial should be conducted to define the role of CRT implantation in patients with CKD [10]. Despite some interesting observations and results, in our opinion, the current research work has its limitations.…”
Section: Variablementioning
confidence: 84%
See 1 more Smart Citation
“…From a large meta-analysis of published studies, it is known that the use of CRT in patients with CKD positively affects patient survival; however, the mechanism by which this occurs is unknown. e authors of our study strongly recommend that a randomized controlled trial should be conducted to define the role of CRT implantation in patients with CKD [10]. Despite some interesting observations and results, in our opinion, the current research work has its limitations.…”
Section: Variablementioning
confidence: 84%
“…Resynchronization therapy (CRT) is a well-established treatment for patients with clinically apparent heart failure, decreased left ventricular ejection fraction (LVEF), and prolonged QRS duration on surface electrocardiogram (ECG) [9]. It is also known that CRT implantation reduces mortality in the CKD population overall [10]. Also, patients with renal dysfunction are poorly represented in CRT clinical trials, which results in a lack of evidence to guide treatment in this high-risk group [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus it further demonstrates that CRT(D) could improve survival prognosis in comparison with ICD in CKD patients. Similarly, a meta‐analysis of 21,000 patients showed that compared with ICD, patients with CRT have a lower risk of all‐cause death (OR = 0.73; 95% CI, 0.57 to 0.92; p = 0.01) 43 . Compared with ICD, CRT(D) is more consistent with physiological pacing.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, patients with ESKD receiving ICDs have a significantly increased risk of developing procedure-related complications [21]. On the other hand, in some studies, a potentially beneficial effect of ICDs in this patient population was described [22][23][24].…”
Section: Cied Evidence In Ckd Patientsmentioning
confidence: 99%
“…Thankfully, cardiac resynchronization therapy (CRT) outcomes in patients with systolic heart failure and CKD are clearly more positive, despite a more complex implantation procedure [24][25][26]. Effective left ventricle reverse remodeling plays a vital role in preserving renal function, regardless of the degree of baseline renal insufficiency [27].…”
Section: Cied Evidence In Ckd Patientsmentioning
confidence: 99%